Ambiguitas Pekerja Anak Siber: Menggugat Eksploitasi Kidfluencer pada Ekosistem Gig Economy di Indonesia - Sayid Muhammad Rifki Noval (Universitas Muhammadiyah Kotabumi, 2026)
This study falls within the disciplinary area of cyber law, labor law, and consumer protection law. It aims to analyze the legal void surrounding the commercial exploitation of kid influencers in the digital gig economy and propose a reconstructed legal protection regime in Indonesia. The selection of this topic is driven by the alarming rise of child monetization disguised as family documentation (sharenting), which leaves minors highly vulnerable to structural exploitation by parents, marketing agencies, and algorithmic platform designs. Employing a normative legal research methodology with statutory and conceptual approaches, the study hypothesizes that kid influencer activities fulfill the criteria of a disguised employment relationship that conventional legal frameworks fail to address. The main findings reveal a chronic regulatory paralysis, children are denied standard labor protections such as working hour limits, lack intellectual property rights over their digital creations, and possess no financial trust safeguards for their earnings. Furthermore, the prevalent practice of backdoor advertising severely violates consumer protection norms by manipulating public trust. The research contributes to the field by proposing a sui generis regulatory framework that mandates strict professional status recognition for child creators, compulsory income-safeguarding trusts, and transparent sponsorship disclosures. Ultimately, the significance of these conclusions lies in providing a robust legal foundation to dismantle modern digital slavery, hold platforms and parents legally accountable through restorative justice, and safeguard the fundamental human rights and future of children in the digital civilization.